2008
DOI: 10.1158/0008-5472.can-07-5991
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Genetic Variants in MicroRNA-Related Genes and Risk of Bladder Cancer

Abstract: MicroRNAs (miRNA) are small noncoding RNA molecules involved in a diversity of cellular functions. Although it has been reported that global suppression of the miRNA biogenesis pathway leads to enhanced tumorigenesis, the effect of common genetic variants of miRNA-related genes on cancer predisposition is unclear. To better understand this effect, we genotyped 41 single-nucleotide polymorphisms (SNP) from 24 miRNA-related genes in a case-control study conducted in 746 Caucasian patients with bladder cancer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
185
1
6

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(212 citation statements)
references
References 47 publications
(55 reference statements)
12
185
1
6
Order By: Relevance
“…Recently, SNPs that could affect response to miRs were noted in miR target site sequences (159,160). Correlations between miR polymorphisms and SNPs in miR target sites with risk of bladder and colorectal cancers were reported (161)(162)(163). Hence, examination of SNPs in miR-binding sites may also provide key insights into various human diseases.…”
Section: Clinical Applications Therapeutic Strategies and Perspectivesmentioning
confidence: 99%
“…Recently, SNPs that could affect response to miRs were noted in miR target site sequences (159,160). Correlations between miR polymorphisms and SNPs in miR target sites with risk of bladder and colorectal cancers were reported (161)(162)(163). Hence, examination of SNPs in miR-binding sites may also provide key insights into various human diseases.…”
Section: Clinical Applications Therapeutic Strategies and Perspectivesmentioning
confidence: 99%
“…[9][10][11][12][13] It is possible that association of miRNA polymorphisms may be cancer specific. However, the non-significant results of our study could be explained because of inherent difficulties in validating and replicating association studies with complex traits such as cancer and/or as a consequence of ethnic variation.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 Various single nucleotide polymorphisms (SNPs) are known to exist in miRNA genes, which can lead to variations in the quantity of miRNAs resulting in diverse functional consequences and, therefore, may represent ideal candidate biomarkers for cancer prognosis. 8 Various genetic association studies have explored the function of pre-miRNA polymorphisms in cancers including non-small cell lung cancer (NSCLC), 9 breast cancer, 10 hepatocellular carcinoma, 11 bladder cancer 12 and papillary thyroid carcinoma. 13 However, the function of genetic variants of miRNA genes in GBC is yet to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al 56 studied 100 human tumor tissues and 20 cancer cell lines and have identified a mutation in miRNA let-7e that causes a significant reduction of its expression in vivo contributing to tumorigenesis. A similar study by Yang et al 57 has genotyped several SNPs from miRNA genes in 746 matched normal and bladder cancer tissues and discovered that SNPs in GEMIN3 gene can affect miRNA binding, thereby significantly increasing bladder cancer risk.…”
Section: Micrornas In Complex Diseasesmentioning
confidence: 95%